Carabin Protects Against Cardiac Hypertrophy by Blocking Calcineurin, Ras, and Ca2+/Calmodulin-Dependent Protein Kinase II Signaling. Issue 4 (27th January 2015) - Bisserier, Malik; Berthouze-Duquesnes, Magali; Breckler, Magali; Tortosa, Florence; Fazal, Loubina; de Régibus, Annélie; Laurent, Anne-Coline; Varin, Audrey; Lucas, Alexandre; Branchereau, Maxime; Marck, Pauline; Schickel, Jean-Nicolas; et al.
<x xml:space="preserve">Abstract</x> Background— Cardiac hypertrophy is an early hallmark during the clinical course of heart failure and is regulated by various signaling pathways. However, the molecular mechanisms that negatively regulate these signal transduction pathways remain poorly understood. Methods and Results— Here, we characterized Carabin, a protein expressed in cardiomyocytes that was downregulated in cardiac hypertrophy and human heart failure. Four weeks after transverse aortic constriction, Carabin-deficient (Carabin−/−) mice developed exaggerated cardiac hypertrophy and displayed a strong decrease in fractional shortening (14.6±1.6% versus 27.6±1.4% in wild type plus transverse aortic constriction mice; P<0.0001). Conversely, compensation of Carabin loss through a cardiotropic adeno-associated viral vector encoding Carabin prevented transverse aortic constriction–induced cardiac hypertrophy with preserved fractional shortening (39.9±1.2% versus 25.9±2.6% in control plus transverse aortic constriction mice; P<0.0001). Carabin also conferred protection against adrenergic receptor–induced hypertrophy in isolated cardiomyocytes. Mechanistically, Carabin carries out a tripartite suppressive function. Indeed, Carabin, through its calcineurin-interacting site and Ras/Rab GTPase–activating protein domain, functions as an endogenous inhibitor of calcineurin and Ras/extracellular signal-regulated kinase prohypertrophic signaling. Moreover, Carabin reduced Ca2+/calmodulin-dependent protein kinase II activation and prevented nuclear export of histone deacetylase 4 after adrenergic stimulation or myocardial pressure overload. Finally, we showed that Carabin Ras–GTPase–activating protein domain and calcineurin-interacting domain were both involved in the antihypertrophic action of Carabin. Conclusions— Our study identifies Carabin as a negative regulator of key prohypertrophic signaling molecules, calcineurin, Ras, and Ca2+/calmodulin-dependent protein kinase II and implicates Carabin in the development of cardiac hypertrophy and failure.